Synthesis of some novel enzyme inhibitors and antibacterial agents derived from 5-(1-(4-tosyl)piperidin-4-yl)-1,3,4-oxadiazol-2-thiol (Brazilian Journal of Pharmaceutical Sciences, 2016)
Keeping in mind the pharmacological importance of the 1,3,4-oxadiazole moiety, a series of new S-substituted derivatives, 5a-h, of 5-(1-(4-tosyl)piperidin-4-yl)-1,3,4-oxadiazol-2-thiol (3) were synthesized. The reaction of p-toluenesulfonyl chloride (a) and ethyl isonipecotate (b) produced ethyl 1-(4-tosyl)piperidin-4-carboxylate (1) which was further transformed into 1-(4-tosyl)piperidin-4-carbohydrazide (2) by hydrazine hydrate in methanol. Compound 2 was refluxed with CS2 in the presence of KOH to synthesize 5-(1-(4-tosyl)piperidin-4-yl)-1,3,4-oxadiazol-2-thiol (3). The desired compounds, 5a-h, were synthesized by stirring 3 with aralkyl halides, 4a-h, in DMF using NaH as an activator. The structures of synthesized compounds were elucidated by 1H-NMR, IR and EI-MS spectral studies. These compounds were further evaluated for enzyme inhibitory activity against lipoxygenase and alpha-glucosidase, along with antibacterial activity against Gram-negative and Gram-positive bacteria.